Experimental and numerical study of the PVT design impact on the electrical and thermal performances. (March 2023) - Touti, Ezzeddine; Masmali, Majed; Fterich, Mohamed; Chouikhi, Houssam
Abstract: In terms of energy efficiency, photovoltaic thermal (PVT) systems have great potential to produce simultaneously heat and electricity. PVT solar air collectors are often used in various applications due to their simple structure and low installation cost. While the overall performance of PVT is closely correlated with its design. In this paper, one proposes to design a novel prototype of PVT air collector, in order to improve the electrical and thermal performances. The presented numerical and Experimental studies are carried out to evaluate the impact of the designed prototype on the PVT efficiency. The essential goal of this work is to identify the optimal geometrical and operational PVT air collector parameters with square tube channel. To achieve this goal, numerical simulation using COMSOL Multiphysics is combined with experimental validation of the PVT system. The objective of the optimization consists on improving the output temperature suitable for drying applications firstly, and cooling PV modules by reducing their temperature in order to improve the electrical characteristics such as power and voltage and thereby the efficiency of the photovoltaic modules. Therfore, the PV panel temperature dropped from 53.37 °C to 42.5 °C when the design varies from PVT-1 to PVT-6. Nevertheless, PVT-5 was retained because it has the most appropriate design which gives the best overall efficiency 58.48%. Finally, it should be remembered that the tests were carried out under the same operating conditions namely, the mass flow rate Qm = 0.0235 kg/s at the inlet of the PVT, the inlet temperature (Tint), the ambient temperature (Ta) and the solar irradiation (G).